Planning of spatial development of tourism in the city of Valjevo - Љубица Душков (Mенаџмент у хотелијерству и туризму, 2016)
Planning of tourism development and its spatial disposition represent an important segment of spatial planning. The very fact that tourism can activate other economic branches, and often can be the main development initiator, indicates the importance of the tourism sector in the process of making spatial planning decisions. The valorization of natural and antropogenic potential of tourism development of the city of Valjevo is presented in this paper in order to present an overview of the current situation and problems that exist in this area. On that basis, the concept of spatial development of tourism has been devised which, along with planning priorities defined in the Spatial plan of the municipality, in the future should be one of the developmental components of the entire economy of the planned area.